Malacoplakia: Case report in tongue and review of the literature (2008)
ABSTRACT: Malakoplakia is a relatively uncommon chronic inflammatory reaction of unknown etiology. It usually affects the genitourinary tract but may rarely involve the tongue. There are many theories that explain this reaction but it seems to be the answer to an infectious agent in a patient with immunologic deficiency. Microscopically, malakoplakia is characterized by the presence of foamy histiocytes with distinctive basophilic inclusions, which are known as Michaelis-Gutmann bodies due to a partially ingested bacteria and their posterior calcification. There are many alternatives to treat this entity. We report the only case diagnosed in the tongue, in a 15 years-old male in the Maxillofacial Surgery and Stomatology Service of the Hospital San Vicente de Paúl in Medellín, Antioquia, Colombia.